CircITCH: A Circular RNA With Eminent Roles in the Carcinogenesis - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Taheri, Mohammad; Jamali, Elena (Frontiers in Oncology, 2021)
Circular RNAs (circRNAs) are a group of long non-coding RNAs with enclosed structure generated by back-splicing events. Numerous members of these transcripts have been shown to affect carcinogenesis. Circular RNA itchy E3 ubiquitin protein ligase (circ-ITCH) is a circRNA created from back splicing events in ITCH gene, a protein coding gene on 20q11.22 region. ITCH has a role as a catalyzer for ubiquitination through both proteolytic and non-proteolytic routes. Circ-ITCH is involved in the pathetiology of cancers through regulation of the linear isoform as well as serving as sponge for several microRNAs, namely miR-17, miR-224, miR-214, miR-93-5p, miR-22, miR-7, miR-106a, miR-10a, miR-145, miR-421, miR-224-5p, miR-197 and miR-199a-5p. Circ_ITCH is also involved in the modulation of Wnt/β-catenin and PTEN/PI3K/AKT pathways. Except from a single study in osteosarcoma, circ-ITCH has been found to exert tumor suppressor role in diverse cancers. In the present manuscript, we provided a comprehensive review of investigations that reported function of circ-ITCH in the carcinogenesis.